Equity, opportunity and education in postcolonial Southeast Asia - Joseph, Cynthia; Matthews, Julie (Routledge critical studies in Asian education, 2014)
Equity, Opportunity and Education in Postcolonial Southeast Asia addresses the ways in which colonial histories, nationalist impulses and forces of globalization shape equity and access to education in Southeast Asia. Although increasingly identified as a regional grouping (ASEAN), Malaysia, Indonesia, Burma, Thailand, Singapore and the Philippines are known for their vastly different state structures, political regimes, political economies and ethnocultural and religious demography. This book examines the dimensions of (post)colonialism, nationalism, and globalisation as played out within different international educational contexts.